Contrasting features and responses to treatment of severe chronic active liver disease with and without hepatitis BS antigen. Issue 10 (October 1976) - Schalm, S W; Summerskill, W H; Gitnick, G L; Elveback, L R
Abstract : To determine the clinical implications of HBSAg in severe chronic active liver disease (CALD), patients with HBSAg positive CALD were compared with those chosen by identical clinical, functional, and morphological criteria in whom this test and anti-HBS were negative. HBSAg positive patients were predominantly males over 40 years of age and more frequently failed to respond to conventional treatment programmes with prednisone. HBSAg negative patients were more often female and younger, had a higher incidence of associated immunopathic disease and immunoserological markers in high titre, and more often responded to treatment with full remission of their disease. HBSAg positive patients failing treatment with conventional doses of prednisone often improved with higher doses, but did not reach full remission of their disease. The benefit-risk ratio of both conventional and high doses of prednisone in HBSAg positive severe CALD needs further clarification.